THEORETICAL JUSTIFICATION FOR IMPROVING THE DESIGN OF SPECIAL CLOTHING TO OPTIMIZE ITS DESIGN (Academicia Globe: Inderscience Research, 2023)
The development of scientific and technological progress, and transformations in the field of production at modern industrial enterprises, along with others, bring to the fore the task of optimally solving the issue of ensuring the safety of people in production, including by designing special clothing to protect people from the harmful effects of the production environment. This article discusses the research and development of workwear for workers with high ergonomic, aesthetic, protective and hygienic characteristics, taking into account specific working conditions and the image of the enterprise, which can provide a high overall quality indicator and effective individual protection of workers.